Systematic Literature Review : Pengaruh Teknologi terhadap Gaya Belajar Matematika Peserta Didik - Ariani, Lisa; Ulya, Shofi Nuril; Haq, Ahmad Harisul; Fakhriyana, Dina (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2025)
This study aims to determine the impact of technology use on students’ learning styles in mathematics. The research method employed is a Systematic Literature Review (SLR), collecting data and searching for information using the Publish or Perish 8 application with Google Scholar and Crossref databases within the 2020–2024 timeframe. The Google Scholar database was limited to 100 articles annually, resulting in 467 articles, while the Crossref database yielded 1000. A total of 1467 articles were obtained, then a filter was carried out by adjusting the objectives of the research, and the final result was 18 relevant articles obtained from the filter results using the PRISMA method to see the influence of technology on students who have various learning styles, especially when studying mathematics. The results show that technology enhances the effectiveness of learning for visual, auditory, and kinesthetic learning styles. Applications such as PowerPoint and Quizizz were found to improve learning outcomes for visual learners. Meanwhile, audio-based media like song lyrics and interactive videos are more suitable for auditory learners. GeoGebra and Augmented Reality (AR)-based applications are better suited for kinesthetic learners. Overall, technology that is tailored to students’ needs can significantly increase their motivation and engagement in the learning process.